Streptococcus equi subespécie equi: desenvolvimento de um ELISA indireto e avaliação da influência do processamento do antígeno na capacidade protetora de bacterinas - Guizzo, João Antônio (2022)
Equine adenitis is a highly contagious acute inflammatory disease that affects the upper respiratory tract of horses and responsible for large economic losses and deficit in the performance of affected animals. The etiologic agent, Streptococcus equi subsp. equi (SEE), has a repertoire of virulence factors that combined provide the microorganism with the ability to infect and cause disease in horses. Worldwide, equine adenitis is considered the horse disease with the highest number of notifications. Thus, tools and strategies aimed to improve the prevention of equine adenitis outbreaks are extremely necessary and a matter of investigation in several laboratories worldwide. In this scenario, one of the objectives of this study was the standardization of an ELISA to detect horse antibodies to SEE. The antigen we used was extracted from the surface of SEE cultivated in liquid media. For this purpose, the liquid culture was centrifuged and the bacterial pellet obtained was solubilized in an aqueous solution with 0.025% sodium deoxycholate. After a process of centrifugation and dialysis, the antigen was used to sensitize three different commercial ELISA plates. In addition to the best plate, the best concentrations of antigen and dilution of equine sera were also evaluated. Once optimized, the assay had the following configuration: MaxiSorp® plates, sensitized with 1.2 μg of the extracted antigen, and equine sera tested at a dilution of 1:100. With these settings and a cutoff of OD450nm 0.250, the assay had 100% specificity and 95.9% sensitivity. A second objective of this study was to evaluate in Swiss mice the immunogenicity and protecting capability of 4 different SEE bacterin. For this purpose, two strains of SEE (ATCC and VE) were cultivated and the raw (RA) or processed antigen (PA) was used to formulate four distinct vaccines: ATCC RA, ATCC PA, VE RA and VE PA which were inoculated in mice twice, 14 days apart. Two weeks after the second immunization the mice were challenged intranasally. After the experimental challenge, clinical signs, weight loss, survival and nasal cavity colonization were monitored. At the end of the experiment, 83.3% of the mice vaccinated with formulations based on SEE VE (RA and PA) survived the challenge. Protection in groups immunized with SEE ATCC vaccines varied according to the antigen formulation. With the exception of SEE ATCC PA, all formulations resulted in significantly (p<0.05) higher protection compared to the unvaccinated group. Regardless of the SEE strain, vaccines formulated with RA induced higher IgG titers compared to vaccines containing PA. Of the 4 vaccines developed, the formulation based on the SEE VE RA strain was significantly more immunogenic.